2011 IEEE/RSJ International Conference on Intelligent Robots and Systems 2011
DOI: 10.1109/iros.2011.6048184
|View full text |Cite
|
Sign up to set email alerts
|

Passive dynamic walking of combined rimless wheel and its speeding-up by adjustment of phase difference

Abstract: The design and modeling of a segmented myriapod millirobot with a compliant body is presented. A dynamic model is used to demonstrate how body undulations can result from only varying the phase difference in the stance change between adjacent segments -even with passive intersegmental connections -and how these gaits affect locomotion. Different gaits are demonstrated experimentally in a 20-leg, 2.2 gram millirobot, and the resulting motion is compared to that predicted by the simulation. Both simulation and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Furthermore, through the analysis of serni PDW, the importance of a time delay was suggested. Now we are conducting the experimental tests using our prototype CRW machine [5]. The results will be reported in a future paper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, through the analysis of serni PDW, the importance of a time delay was suggested. Now we are conducting the experimental tests using our prototype CRW machine [5]. The results will be reported in a future paper.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we add convergence speed as a criterion for evaluation of the gait efficiency, and discuss the trade-offs between it and other criteria. For gait analysis, we introduce the model of an active combined rimless wheel (CRW ) that consists of two identical rimless wheels [5] without having the phase difference between the fore and rear legs. This model is 1 F. Asano and X. Xiao are with the School of Information Science, Japan Advanced Institute of Science and Technology, 1-1 Asahidai, Nomi, Ishikawa 923-1292, Japan {fasano, xxiao}@ j aist .…”
Section: Introductionmentioning
confidence: 99%
“…Use of passive dynamics to improve the stability and efficiency of legged locomotion has been the focus of several studies in the recent past [16], [31], [32]. In [27] the authors propose to have permanent springs with damping at the foot of a biped robot in order to be dynamically coupled with the environment.…”
Section: Discussionmentioning
confidence: 99%
“…For simplicity, the rear RW is called "RW1", and the fore one is called "RW2". The CRW model is identical to that in our previous work (see [4] for further detail). We then add a passive wobbling mass to the body frame.…”
Section: Modeling Of Combined Rimless Wheel With Wobbling Massmentioning
confidence: 97%
“…Remy et al investigated a quadruped walker that consists of two compass-like biped and numerically showed that the fore and rear legs' motion synchronizes [3]. Inoue et al investigated modeling and analysis of PDW of a combined rimless wheel (CRW) that consists of two identical eight-legged rimless wheels (RWs), and showed that speeding-up is achieved by adjusting the phase difference between the fore and rear legs through numerical simulations [4]. The validity was also confirmed by using an experimental machine.…”
Section: Introductionmentioning
confidence: 99%